2008
DOI: 10.1073/pnas.0800320105
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic identification and stability of the intermediate in the OH + HONO 2 reaction

Abstract: The reaction of nitric acid with the hydroxyl radical influences the residence time of HONO2 in the lower atmosphere. Prior studies [Brown SS, Burkholder JB, Talukdar RK, Ravishankara AR (2001) J Phys Chem A 105:1605-1614] have revealed unusual kinetic behavior for this reaction, including a negative temperature dependence, a complex pressure dependence, and an overall reaction rate strongly affected by isotopic substitution. This behavior suggested that the reaction occurs through an intermediate, theoretical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 31 publications
4
20
0
Order By: Relevance
“…Most of the experimental studies were carried out in the mid-70s to mid-80s (Margitan et al, 1975;Smith and Zellner, 1975;Wine et al, 1981;Jourdain et al, 1982;Kurylo et al, 1982;Margitan and Watson, 1982;Marinelli and Johnston, 1982;Ravishankara et al, 1982;Devolder et al, 1984;Smith et al, 1984;Connell and Howard, 1985;Jolly et al, 1985;Stachnik et al, 1986) with only the most recent and comprehensive studies of the reaction (Brown et al, 1999(Brown et al, , 2001) extending the temperature range to those found at the tropopause. Experimental (Carl et al, 2001;McCabe et al, 2003;O'Donnell et al, 2008b) and theoretical (Xia and Lin, 2001;Gonzalez and Anglada, 2010) work examining the details of the reaction mechanism highlight continuing interest in this complex reaction, which proceeds via formation of a pre-reaction complex, HO-HNO 3 (Aloisio and Francisco, 1999;Brown et al, 1999Brown et al, , 2001Xia and Lin, 2001;O'Donnell et al, 2008a). HO-HNO 3 can (a) dissociate into reactants, (b) rearrange to form products via a transition state which lies somewhat higher in energy than the reactants or (c) experience collisional deactivation by bath gas molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the experimental studies were carried out in the mid-70s to mid-80s (Margitan et al, 1975;Smith and Zellner, 1975;Wine et al, 1981;Jourdain et al, 1982;Kurylo et al, 1982;Margitan and Watson, 1982;Marinelli and Johnston, 1982;Ravishankara et al, 1982;Devolder et al, 1984;Smith et al, 1984;Connell and Howard, 1985;Jolly et al, 1985;Stachnik et al, 1986) with only the most recent and comprehensive studies of the reaction (Brown et al, 1999(Brown et al, , 2001) extending the temperature range to those found at the tropopause. Experimental (Carl et al, 2001;McCabe et al, 2003;O'Donnell et al, 2008b) and theoretical (Xia and Lin, 2001;Gonzalez and Anglada, 2010) work examining the details of the reaction mechanism highlight continuing interest in this complex reaction, which proceeds via formation of a pre-reaction complex, HO-HNO 3 (Aloisio and Francisco, 1999;Brown et al, 1999Brown et al, , 2001Xia and Lin, 2001;O'Donnell et al, 2008a). HO-HNO 3 can (a) dissociate into reactants, (b) rearrange to form products via a transition state which lies somewhat higher in energy than the reactants or (c) experience collisional deactivation by bath gas molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the experimental studies were carried out in the mid-70s to mid-80s (Margitan et al, 1975;Smith and Zellner, 1975;Wine et al, 1981;Jourdain et al, 1982;Kurylo et al, 1982;Margitan and Watson, 1982;Marinelli and Johnston, 1982;Ravishankara et al, 1982;Devolder et al, 1984;Smith et al, 1984;Connell and Howard, 1985;Jolly et al, 1985;Stachnik et al, 1986) with only the most recent and comprehensive studies of the reaction (Brown et al, 1999(Brown et al, , 2001 extending the temperature range to those found at the tropopause. Experimental (Carl et al, 2001;McCabe et al, 2003;O'Donnell et al, 2008b) and theoretical (Xia and Lin, 2001;Gonzalez and Anglada, 2010) work examining the details of the reaction mechanism highlight continuing interest in this complex reaction, which proceeds via formation of a pre-reaction complex, HO-HNO 3 (Aloisio and Francisco, 1999;Brown et al, 1999Brown et al, , 2001Xia and Lin, 2001;O'Donnell et al, 2008a). HO-HNO 3 can (a) dissociate into reactants, (b) rearrange to form products via a transition state which lies somewhat higher in energy than the reactants or (c) experience collisional deactivation by bath gas molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Another often-investigated ion influencing AOP and SR-AOP reactions is nitrate. The reaction with a hydroxyl radical of its conjugate acid (nitric acid) was investigated theoretically, and a hydrogen-bonded OH-HONO 2 intermediate was confirmed with an estimated lifetime of ∼40 ps [98]. A similar investigation was the subject of another work [73].…”
Section: Reactions Of •Oh With Other Water Matrix Constituentsmentioning
confidence: 85%